2017
DOI: 10.18326/rgt.v10i1.813
|View full text |Cite
|
Sign up to set email alerts
|

Toward Mobile-Assisted Language Learning (MALL): Reaping Mobile Phone Benefits in Classroom Activities

Abstract: ENGLISH ABSTRACT Mobile phone has been studied by researchers in its connection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
0
9
0
2
Order By: Relevance
“…According to their opinion, it was clear that feature of audio video player in their mobile phone helped them in learning proces as the previous research had proven (Smythe & Neufeld 2010). Mobile phone can be used to gain its benefit in ELL activities in Indonesian IHE (Yudhiantara & Nasir 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to their opinion, it was clear that feature of audio video player in their mobile phone helped them in learning proces as the previous research had proven (Smythe & Neufeld 2010). Mobile phone can be used to gain its benefit in ELL activities in Indonesian IHE (Yudhiantara & Nasir 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mobile application can facilitate her in delivering the material and make students more interested in learning English, because she make use of something that is familiar with students. This is supported by prior research by Yudhiantara & Nasir (2017) mobile phones provides benefits that can be obtained by students in supporting classroom activities and learning English.…”
Section: The Importance Of Technology and Mobile Applicationmentioning
confidence: 65%
“…A number of researches related to mobile learning in the classroom have been conducted by Yudhiantara & Nasir (2017) showed that students had positive attitude toward mobile phone to support classroom process. Another study, Syafitri, et (2018) focused on implementing Powtoon as a media to improve the students" pronunciation in speaking class.…”
Section: Introductionmentioning
confidence: 99%
“…These possiblities need to be considered and embraced. Massive number of studies show that the use of technologhy at the classroom facilitate and promote learning process (Plester, Wood, & Joshi, 2009in Yudhiantara & Nasir, 2017Bull andThompson, 2004 in Yudhiantara &Nasir, 2017;Smythe & Neufeld, 2010in Yudhiantara & Nasir, 2017Sha, Looi, Chen, & Zhang, 2012in Yudhiantara & Nasir, 2017Lee, Lee & Kweon, 2013in Yudhiantara & Nasir, 2017. This era, the fourth revolution industrial, leaves a vacuum that needed to be filled out.…”
Section: Introductionmentioning
confidence: 99%